2021
DOI: 10.1007/s13198-021-01367-6
|View full text |Cite
|
Sign up to set email alerts
|

Order diminution and its application in controller design using salp swarm optimization technique

Abstract: Order diminution (OD) or model order reduction (MOR), a very important field of System Engineering, has been explored by many researchers. Different methods are available for reducing the complexity of a control system, which are subsequently utilized to get a cost-effective controller. Model order reduction is done by either using classical methods or by using optimization techniques. In optimization algorithms, accuracy, complexity, and convergent rate are the main criteria for comparison in OD. This paper c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Consider a unity feedback system with feed-forward transfer function G ( s ) G c ( s ) as shown in Figure 1. Let G(s) be the transfer function of the reduced-order model (Ahamed et al, 2022a, 2022b; Prajapati et al, 2020; Prajapati and Prasad, 2019, 2020, 2020b, 2022) for the original higher order plant to be controlled and G c ( s ) the transfer function of the proposed compensator to be designed in this section.
Figure 1.Feedback system.
…”
Section: Proposed Compensator Design Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…Consider a unity feedback system with feed-forward transfer function G ( s ) G c ( s ) as shown in Figure 1. Let G(s) be the transfer function of the reduced-order model (Ahamed et al, 2022a, 2022b; Prajapati et al, 2020; Prajapati and Prasad, 2019, 2020, 2020b, 2022) for the original higher order plant to be controlled and G c ( s ) the transfer function of the proposed compensator to be designed in this section.
Figure 1.Feedback system.
…”
Section: Proposed Compensator Design Algorithmmentioning
confidence: 99%
“…Furthermore, these methods had drawbacks such as non-uniqueness, pole clustering, gain adjustment and difficulty to maintain the dominant roots in the lower order system for non-minimum higher order plants. Ahamed et al (2022a, 2022b), Prajapati and Prasad, 2019, 2020, 2020b, 2022 and Prajapati et al (2020) have presented a number of reduction techniques to overcome these drawbacks, guaranteeing the stability of lower order models in addition to reproducing the behaviour of the original large-scale model for a number of higher order systems. These studies have shown that the reduced-order models produced by Mihailov stability, enhanced Pade approximation and truncation, improved generalized pole clustering, moment matching and salp swarm optimization approaches not only reflect the behaviour of the original large-scale model methods but also ensure the stability of the reduced-order models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By adjusting the parameter settings, a controller enhances the system's transient and steady-state performance. Till now, several controllers such as PID controller [1][2][3][4], cascade controller [5], fractional order PID (FO-PID) [6][7][8][9][10], proportional integral double derivative (PIDD) [11], dual proportional integral [12], tilt integral derivative controller [13], fuzzy-PID [14][15][16][17], state feedback control [18], adaptive neurofuzzy inference system [16], H-infinity controller [19,20], model predictive control [21], nonlinear model predictive control [22], adaptive model predictive control [23] have been developed. But the basic PID controller is widely used in all most all industries regardless of meaningful development in the control area during recent years because of its easy implementation, simple construction, working principle, and maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…Such endeavour has, nonetheless, been overshadowed by subsequent publication from Singh [13] in 2018, which successfully proposed the Sine Cosine Algorithm (SCA) as a superior MOR algorithm for high-order continuous structure against other efficacious order-reduction methods, including PSO, Elephant Herding Optimization (EHO) and Nelder-Mead Simplex Algorithm (NMSA), while maintaining an admirable operational simplicity. Moreover, optimization approaches, such as Harris Hawk Optimization (HHO) [14] and Salp Swarm Optimization (SSO) [15], have simultaneously emerged as exploitable algorithmic alternatives within modern academic and real-time MOR applications. With efficiency being established as a fundamental basis for the presumed effectiveness of the aforementioned MOR algorithms, estimating the precision of an order-reduced model would, therefore, be determined by the theoretical robustness of the specified optimization method.…”
Section: Introductionmentioning
confidence: 99%